Unemployment Benefits: Disincentives to Work? - Chincharauli, Tamunia (Caucasus Journal of Social Sciences, 2013)
The aim of this paper is to analyze the effect that unemployment benefits – an instrument of social policy – have on incentives to work. It will start by discussing arguments that portray unemployment benefits as disincentives. It will continue by analyzing more profoundly how benefits can serve as an instrument to increase employment and mitigate disincentives to work. Finally, it will be shown that when taking into consideration the heterogeneity of elements shaping the unemployment benefit system and structure, substantial replacement rates may contribute to increasing efficiency of labor market.